Determination of some metals and polyatomic ions in bottled water - Estabraq Ali Hameed (Genius Journals, 2022)
Regularly evaluating bottled water in the market is very necessary. There are different types of locally made or imported water in the market. To preserve the health of citizens, it was necessary to conduct chemical, physical and biological analyzes to determine its suitability for human consumption. Some may think that the process of evaluating the levels of minerals, salts and compounds in drinking water is not necessary, and the trend towards medical and scientific issues will be better. The source of infection with many diseases is caused by water pollution and the implementation of experiments related to scientific topics need clean water free of pollution. Therefore, the levels of some minerals in bottled water samples such as iron, zinc, aluminum, copper and magnesium were evaluated using a spectrophotometer, as well as the evaluation of sulfate ions, silicates, nitrates and nitrites, as well as ammonia and ammonium. Through the results, there were deviations and the presence of high concentrations of some minerals and ions when compared with the standard specifications. Approved for bottled drinking water
Keywords: Bottled water; ions; salts; spectrophotometer